Thinking for a Change : 11 Ways Highly Successful People Approach Life and Work - Maxwell, John C., 1947- (New York Center Street, 2005)
At the heart of John C. Maxwell's brilliant and inspiring book is a simple premise: To do well in life, we must first think well. But can we actually learn new mental habits? Thinking for a Change answers that with a resounding "yes"--And shows how changing your thinking can indeed change your life. Drawing on the words and deeds of many of the world's greatest leaders and using interactive quizzes, this empowering book helps you assess your thinking style, guides you to new ones, and step by step teaches you the secrets of: a- big-Picture Thinking-seeing the world beyond your own needs and how that leads to great ideas; b- focused Thinking-removing mental clutter and distractions to realize your full potential; c- creative Thinking-stepping out of the "box" and making breakthroughs; d- shared Thinking-working with others to compound results; e- reflective Thinking-looking at the past to gain a better understanding of the future ... and much more. -- description from http://www.leadershipnow.com (Oct. 5, 2011).
Include Notes
Keywords: Success in business -- Attitude change -- Creative thinking